Differential Effects of Parietal and Cerebellar Stroke in Response to Object Location Perturbation - Pelton, Trudy A.; Wing, Alan M.; Fraser, Dagmar; van Vliet, Paulette (Frontiers in Human Neuroscience, 2015)
Background: The differential contributions of the cerebellum and parietal lobe to coordination between hand transport and hand shaping to an object, have not been clearly identified. Objective: To contrast impairments in reach to grasp coordination, in response to object location perturbation, in patients with right parietal and cerebellar lesions, in order to further elucidate the role of each area in reach to grasp coordination. Method: A two-factor design with one between subject factor (right parietal stroke; cerebellar stroke; controls) and one within subject factor (presence or absence of object location perturbation) examined correction processes used to maintain coordination between transport to grasp in the presence of perturbation. Sixteen chronic stroke participants (8 with right parietal lesions and 8 with cerebellar lesions) were matched in age (mean=61years; standard deviation=12) and hand dominance with 16 healthy controls. Hand and arm movements were recorded during unperturbed baseline trials (10) and unpredictable trials (60) in which the target was displaced to the left (10) or right (10) or remained fixed (40). Results: Cerebellar patients had a slowed response to perturbation with anticipatory hand opening, an increased number of aperture peaks and disruption to temporal coordination, and greater variability. Parietal participants also exhibited slowed movements, with increased number of aperture peaks, but in addition, increased the number of velocity peaks and had a longer wrist path trajectory due to difficulties planning the new transport goal and thus relying more on feedback control. Conclusion: Patients with parietal or cerebellar lesions showed some similar and some contrasting deficits. The cerebellum was more dominant in controlling temporal coupling between transport and grasp components, and the parietal area was more concerned with using sensation to relate arm and hand state to target position.